Effects of Anacardium Occidentale Extract on Histopathology and Hepato- Renal Function Tests in Rats - MR Heidari (Babol University of Medical Sciences, 2011)
BACKGROUND AND OBJECTIVE: In Iranian traditional medicine, the core of the fruit of Anacardium occidentale (A.O) was used for relief of pain. Significant analgesic effect of A.O methanolic extract was reported previously. By considering the hepato-renal adverse effects of common analgesic drugs, therefore the hepatorenal toxicity of percolated extract of A.O were investigated in this study. METHODS: In this experimental study, 30 male rats between 190-270 g weight (five groups of six male rats in each group) were used. The extract was administered orally to three groups of 6 male rats with doses of 200, 400 and 800mg/kg every 24 hours for 7 days. Normal saline was administered 5ml/kg, in control group. One other control group was used without any treatment (Sham). At the end of 7th day, urine, blood and tissue specimen were collected for analysis. In second phase of the experiment, the blood enzymes including Alanin transpherase (ALT), Aspartate transpherase (AST), Alkalin phosphatase (ALP), and the serum creatinin (Cr), and the Blood Urea Nitrogen (BUN) and urinary enzymes activity including gama-glutamil transpherase (GGT), and lactate dehydrogenase (LDH), changes in the left kidney weight were determined. In third phase of the experiment, histopatological study in kidney and liver were evaluated.FINDINGS: Renal function tests showed, there were no significant differences in BUN and creatinin levels of the control and extract treated groups, and histopathological studies showed no changes in tubules of kidneys, but there was little changes at doses of 800mg/kg. There were significant increases in AST levels at doses of 400 and 800mg/kg (p<0.05) but there was a significant decrease in ALT levels only at doses of 400mg/kg (p<0.01). There was a significant decrease in ALP levels in 200mg/kg group in comparison to Sham groups (p<0.01). The histopathologic studies of liver showed evidence of hepatotoxicity with high dose of 800mg/kg.CONCLUSION: The results showed no hepatorenal toxicity after oral administration of 200 and 400mg/kg methanolic extract of (A.O). But there were some evidences for hepatorenal toxicity with higher doses of extract, 800mg/kg (A.O). Since therapeutic analgesic dose (200 mg/kg) of A.O did not induce any hepatorenal toxicity, therefore it seems that the A.O is a suitable plant for further investigation for introducing as analgesic drug for clinical use.